Volume 2A: Turbomachinery 2018
DOI: 10.1115/gt2018-76873
|View full text |Cite
|
Sign up to set email alerts
|

On the Periodically Unsteady Interaction of Wakes, Secondary Flow Development and Boundary Layer Flow in an Annular LPT Cascade: Part 2 — Numerical Investigation

Abstract: In this work we present the results of the numerical investigations concerning interaction effects between periodically incoming wakes, secondary flow development and boundary layer flow inside a low pressure turbine (LPT) equipped with modified T106-profile blades. The numerical predictions obtained using 3D Unsteady Reynolds-Averaged Navier-Stokes (URANS) simulations are compared against stationary and time resolved experimental results conducted in the same configuration and discussed in part 1 of this 2-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, especially in the hub region, a distinction between passage vortex (PV) and the pressure side leg of the horse shoe vortex (HSV-PL) is enabled for t/T BP = 1/3, as the HSV-PL slides beneath the PV and pushes it along the suction side trailing edge radially inward, before it blends again with the PV. As could be shown in detail in [52,53,55,56], this periodic and short-duration event is based on the upstream wake impact on the developing HSV-PL, which is massively diverted in the front part of the blade passage by the impinging wake structure. Also, the unsteadiness of the suction side corner separation, shaping the concentrated shed vortex (CSV) can be realized.…”
Section: Impact On the Secondary Flow Structuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, especially in the hub region, a distinction between passage vortex (PV) and the pressure side leg of the horse shoe vortex (HSV-PL) is enabled for t/T BP = 1/3, as the HSV-PL slides beneath the PV and pushes it along the suction side trailing edge radially inward, before it blends again with the PV. As could be shown in detail in [52,53,55,56], this periodic and short-duration event is based on the upstream wake impact on the developing HSV-PL, which is massively diverted in the front part of the blade passage by the impinging wake structure. Also, the unsteadiness of the suction side corner separation, shaping the concentrated shed vortex (CSV) can be realized.…”
Section: Impact On the Secondary Flow Structuresmentioning
confidence: 98%
“…The presented investigations give a brief outline of key findings from recent publications by the authors, where the unsteady impact of periodic bar wakes on the flow field downstream of the stator row as well as on the stator profile pressures and boundary layers were discussed. For details, please see [51][52][53][54][55][56][57][58].…”
Section: Sub-project D-influence Of Periodic Wakes On the Transient Near-wall Flow In Anmentioning
confidence: 99%
“…They found that the wake reduced the end-wall secondary flow losses at higher Reynolds number [21]. Winhart et al analyzed the complex interactions between the wake, the secondary flow structure and the boundary layer flow to determine the contribution of the secondary flow components to the turbulent kinetic energy [22,23]. Darji studied the generation location of horseshoe vortices and the development pattern of endwall flow under different working conditions [24].…”
Section: Introductionmentioning
confidence: 99%